2015
DOI: 10.1515/joepi-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Neurostimulation, neuromodulation, and the treatment of epilepsies

Abstract: SUMMARYIntroduction. Neurostimulation and neuromodulation are techniques that may be able to affect the course of epilepsy. In the last 20 years, since the approval of VNS, we have observed a surge of studies assessing the potential of other devices and techniques for the treatment of pharmacoresistant epilepsies including deep brain stimulation (DBS), responsive neurostimulation (RNS), trigeminal nerve stimulation (TNS), transcranial direct current stimulation (tDCS), and repetitive transcranial magnetic stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 98 publications
(131 reference statements)
0
8
0
Order By: Relevance
“…In this meta-analysis, random-effects analysis revealed a pooled standardized effect size (Hedge's g) of 0.476, indicating a medium effect size favoring active stimulation over sham stimulation in the reduction of craving. No signi cant differences were found between the two brain stimulation techniques, even though their mechanisms of action are somewhat different [11,19]. Regarding rTMS more speci cally, a more recent systematic review, including 26 articles and 748 patients, showed signi cant reductions in cravings and substance use [20].…”
Section: Manuscript Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In this meta-analysis, random-effects analysis revealed a pooled standardized effect size (Hedge's g) of 0.476, indicating a medium effect size favoring active stimulation over sham stimulation in the reduction of craving. No signi cant differences were found between the two brain stimulation techniques, even though their mechanisms of action are somewhat different [11,19]. Regarding rTMS more speci cally, a more recent systematic review, including 26 articles and 748 patients, showed signi cant reductions in cravings and substance use [20].…”
Section: Manuscript Backgroundmentioning
confidence: 99%
“…Patients will be excluded if they have, at the inclusion visit, any of the following: (1) breath-alcohol concentration (BAC) > 0 milligrams per liter of exhaled air, (2) less than 6 heavy drinking days (HDD) in the previous 4 weeks (de ned as more than 60 grams of pure alcohol in men and 40 grams in women consumed in one day) [1], (3) average alcohol consumption below the medium risk level according to World health Organization (WHO) in the previous 4 weeks (≤ 40g/day for men; ≤ 20g/day for women) [22], (4) more than 3 days of abstinence prior to inclusion, (5) a revised Clinical Institute Withdrawal Assessment (CIWA) for Alcohol score ≥ 10 (indicating the need for medication-supported detoxi cation), (6) concomitant treatment with disul ram, acamprosate, topiramate, baclofene, naltrexone, or nalmefene; (7) a history of pre-delirium tremens and delirium tremens; (8) DSM-5 substance use disorder other than alcohol or tobacco use disorder; (9) acute psychiatric disorders that have required hospitalization and/or immediate adjustment of psychotropic medications; (10) severe major depression, as de ned by 17-item Hamilton Depression scale (HAM-D) ≥ 24 [23]; (11) recent change in psychotropic medication (< 1 month); ( 12) severe chronic psychiatric disorders including schizophrenia, paranoia and bipolar disorder type I and II; (13) advanced liver, kidney, cardiac, or pulmonary disease or other acute serious or unstable medical conditions that would compromise a patient's participation in the study according to the physician's judgment; (14) contra-indications to rTMS: personal history of convulsive seizures, cerebral vascular accident, pacemaker, neurosurgical clips, carotid or aortic clips, heart valves, hearing aid, ventricular bypass valve, sutures with wires or staples, foreign objects in the eye, shrapnel, other prosthesis or intracranial ferromagnetic material; (15) women who are pregnant or lactating; (16) women of childbearing potential with a positive urine β-human chorionic gonadotrophin pregnancy test at inclusion; (17) concurrent participation in another trial; employees of the investigator or trial site; patients protected by law; (18) persons who are not covered by national health insurance; (19) patients, in the opinion of the investigation, not able to complete the TimeLine Follow-Back (TLFB) and to record their daily alcohol consumption in a diary (derived from the TLFB) during the 3 months of the study; (20) patients who refused to sign the consent form and "safety agreement".…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…2 The efficacy of VNS for the treatment of drug-resistant seizures was proven in four randomized controlled trials with pooled mean percentage decrease in seizure frequency at the last follow-up of 34% and pooled probability of being a responder (≥50% seizure reduction) of 42.7%. 1,3 While these numbers indicate reasonable efficacy, one may ask if there is a possibility of adjusting or ª 2024 LivaNova USA, Inc. Annals of Clinical and Translational Neurology published by Wiley Periodicals LLC on behalf of American Neurological Association. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.…”
Section: Introductionmentioning
confidence: 99%
“…Open‐loop vagus nerve stimulation (VNS) therapy has been a staple for the management of patients with difficult to control focal‐onset seizures with the approval age starting as early as 4 years. This therapy is also frequently used for the treatment of patients with generalized and other seizure types 1 . The stimulation parameters and adjustment methods have remained relatively unchanged over time 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Neuromodulation technologies have been important developments in epilepsy treatment in recent decades [5][6][7][8]. Compared to traditional neuromodulation tools, ultrasound deep brain stimulation (UDBS) is a non-invasive, novel technology with deep penetration and high spatial resolution [9].…”
Section: Introductionmentioning
confidence: 99%